Household air pollution and personal exposure from burning firewood and yak dung in summer in the eastern Tibetan Plateau. (August 2020) - Ye, Wenlu; Saikawa, Eri; Avramov, Alexander; Cho, Seung-Hyun; Chartier, Ryan
Abstract: This study assessed the sources, magnitudes, and chemical compositions of household air pollution (HAP) and personal exposure in traditional Tibetan households. We measured 24-h personal exposures to PM2.5 and kitchen area black carbon (BC) concentrations, using MicroPEMs and microAeths, respectively. Particulate polycyclic aromatic hydrocarbon (PAH) and inorganic element concentrations were quantified via post analyses of a subset of MicroPEM sample filters. Household surveys regarding participant demographics, cookstove usage, household fuel, cooking behaviors, and lifestyles were collected. The results reaffirm that burning firewood and yak dung, mainly for cooking, leads to high PM2.5 and BC exposures. The geometric mean concentration (95% confidence interval, CI) was 74.3 (53.6, 103) μg/m 3 for PM2.5 and the arithmetic mean ± standard deviation (SD) concentration was 4.90 ± 5.01 μg/m 3 for BC and 292 ± 364 ng/m 3 for 15 identified PAHs, respectively. The arithmetic mean ± SD of mass concentrations of 24 detected elements ranged from 0.76 ± 0.91 ng/m 3 (Co) to 1.31 ± 1.35 μg/m 3 (Si). Our statistical analyses further illustrated that the high concentrations of PM2.5, BC, and most PAHs and metals, are significantly associated with nomadic village, poorer stove/chimney conditions and yak dung burning. The results from this study show that substantial HAP exposure is prevalent in Tibetan households and requires immediate actions to mitigate potential negative environmental health impacts. The observational data also revealed the possibility of other important sources (e.g. traffic and garbage burning) that have contributed to personal exposures. These findings improve our understanding of HAP exposure and potential health risks in Tibetan communities and will help inform strategies for reducing HAP in Tibetan households and beyond. Graphical abstract: Image 1 Highlights: The personal exposures to household air pollution in Tibetan households are pervasively high. Distinct diurnal pattern and chemical composition were found in agricultural & nomadic villages. Observed BaP exposure levels were 25–50 times higher than China's national standard. Abstract : 74% of the 24-h personal PM2.5 exposure was above the WHO target and the exposure was significantly higher in households from a nomadic village that primarily burn yak dung with poorer-conditioned stoves/chimneys than those in an agricultural village.